Grooming the wards dynamics between a political party and community groups - Mangada, Ladylyn L. (1996)
The wards or subleaders are the formidable instruments of political elite in capturing and holding on to power. Neither political parties nor community groups are capable of grooming the wards. Recruitment, selection and management of the ward is the sole responsibility of the candidate-politician. This paper focuses on the process/practice in choosing and grooming the wards, highlights the extent of community groups/leaders to bargain, negotiate, and influence party decision and suggest measures how civil society actors can mitigate/weaken patronage politics. The academe, church, real NGOs and media should not abstain from local political involvement.